From an Organometallic Monolayer to an Organic Monolayer Covered by Metal Nanoislands: A Simple Thermal Protocol for the Fabrication of the Top Contact Electrode in Molecular Electronic Devices. Issue 9 (26th June 2014) - Ballesteros, Luz M.; Martín, Santiago; Cortés, Javier; Marqués‐González, Santiago; Pérez‐Murano, Francesc; Nichols, Richard J.; Low, Paul J.; Cea, Pilar
<x xml:space="preserve">Abstract</x> In this contribution, a novel method for practical uses in the fabrication of the top contact electrode in a metal/organic monolayer/metal device is presented. The procedure involves the thermally induced decomposition of an organometallic compound, abbreviated as the TIDOC method. Monolayers incorporating the metal organic compounds (MOCs) [[4‐{(4‐carboxy)ethynyl}phenyl]ethynyl]‐(triphenylphosphine)‐gold, 1, or [1‐isocyano‐4‐methoxybenzene]‐[4‐amino‐phenylethynyl]‐gold, 2, were annealed at moderate temperatures (1: 150 °C for 2h and 2: 100 °C for 2 h), resulting in cleavage of the Au‐P or Au‐C bond and reduction of Au(I) to Au(0) as metallic gold nanoparticles (GNPs). These particles are distributed on the surface of the film resulting in formation of metal/molecule/GNP sandwich structures. Electrical properties of these nascent devices were determined by recording I–V curves with a conductive‐AFM. The I–V curves collected from these metal/organic monolayer/GNPs sandwich structures are typical of metal‐molecule‐metal junctions, with no low resistance traces characteristic of metallic short circuits observed over a wide range of set‐point forces. The TIDOC method is therefore an effective procedure for the fabrication of molecular junctions for the emerging area of molecular electronics.